Effects of siam weed (Chromolaena odorata) on plant parasitic nematodes on tomatoes (Solanum lycopersicum) - Nyong, Adeinbiari; Nworgu, Confidence Ogechi (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
As a result of the damage caused by plant parasitic nematodes in tomato production, a study to ascertain the effect of Chromolaena odorata against the nematode of "Derica” was carried out at the University of Port Harcourt. Plant such as C. odorata was assessed under field assay. This was carried out over 3 months. The undisturbed fields were assessed to determine nematode population. Dried and powdered leaves of C. odorata were administered as organic amendments at 100ml. These were observed over 90 days. However, both soil and root samples were assessed at an interval of 30 days for nematode multiplication. Growth parameters which include height (cm), the weight of root (g), girth (cm), fruit number and weight (g) were also assessed within the 30 days intervals. Data were analysed using Descriptive statistics and ANOVA at a 5% significance level. “Derica” showed susceptibility to Trichodorus and Aphelenchoides spp. for the treatment. Soil nematodes recovered from both untreated and treated fields showed no significant difference (p > 0.05) for the cultivar. “Derica” cultivar recorded no significance in height and girth throughout the period under study (P< 0.05). The application of the extract C. odorata enhanced the production of the fruits. Also, the symptoms of nematode infectivity for treated crops were less than the control. However, results from the "Derica” field showed that treatments are not significant (p> 5%) for gall formation and weights of the roots, though the result showed symptoms of nematode infectivity.